2005
DOI: 10.1159/000088313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Intravenous Immunoglobulin for Patients with MPO-ANCA-Associated Rapidly Progressive Glomerulonephritis

Abstract: Background: To determinewhether intravenous immunoglobulin (IVIg) cancontrol disease activity in patients with myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA)-associated rapidly progressive glomerulonephritis (RPGN). Methods: Twelve patients with serologically and histologically confirmed MPO-ANCA-associated RPGN (7 men, 5 women; mean age 71 ± 3 years) received IVIg (400 mg/kg/day) alone for 5 days. The effects of IVIg were evaluated by white blood cell counts, serum C-reactive protein levels, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In addition, in recent years intravenous administration of h-Ig has been tested in the treatment of other necrotizing vasculitic disorders [17][18][19]. The efficacy of h-Ig in the treatment of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis has gained particular attention [20,21]. It is also known that the myeloperoxidase (MPO)-ANCA titer increases in some acute-stage KD patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in recent years intravenous administration of h-Ig has been tested in the treatment of other necrotizing vasculitic disorders [17][18][19]. The efficacy of h-Ig in the treatment of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis has gained particular attention [20,21]. It is also known that the myeloperoxidase (MPO)-ANCA titer increases in some acute-stage KD patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the effect of renal function on the sTNFR1 and sTNFR2 levels. In the literature, TNF-α, sTNFR1, and sTNFR2 in the serum of MPO-ANCA-associated vasculitis were reported to be higher than in the healthy controls [2, 3]. However, there have been no reports about the surface expression levels of TNFR1 and TNFR2 on the granulocytes in MPO-ANCA-associated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have indicated that tumor necrosis factor (TNF)-α and ANCA together induce the activation of neutrophils, and these activated neutrophils attach to the endothelium, release their toxic granule constituents and oxygen radicals, and thereby cause vascular damage [1]. The plasma TNF-α level in patients with ANCA-associated systemic vasculitis was reported to be increased [2, 3]. However, there are no reports on the expression levels of TNF receptor 1 (TNFR1) and TNF receptor 2 (TNFR2) on granulocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The only 2 randomized trials reported in the literature in which the benefit of IVIG was investigated indicated a significant improvement in patients with GPA and with MPA (9,10). Another study of 12 patients with MPO-ANCA-associated rapidly progressive glomerulonephritis found clinical (50% reduction in the BVAS) and biologic (50% reduction in the CRP level) improvement after a 5-day course of IVIG alone, although there was no control arm (22). A recent series of 5 GPA patients treated with IVIG for opportunistic infections and/or active disease found an 80% remission rate at 9 months, but some of the patients were receiving other immunosuppressive agents in addition to IVIG (23).…”
Section: Crickx Et Almentioning
confidence: 99%